Machining of Polymer Composites - Ahmad, Jamal (Springer US : Imprint: Springer, 2009)
Machining of Polymer Composites is an indispensable reference/source book for process design, tool and production engineers in composite manufacturing and can be used as a textbook for graduate and upper level undergraduate courses in manufacturing and mechanical engineering. Drawing upon years of practical experience and using numerous examples, Jamal Ahmad provides the reader with a comprehensive scientific treatment of the theory of machining as it applies to fiber reinforced polymer composites (FRP), including: Mechanics of chip formation and the critical influence of composite architecture on chip formation mode, cutting forces and surface quality The phenomena of tool wear and an analysis of tool materials and tool wear mechanisms in machining of FRP composites Machinability of FRP composites by traditional and nontraditional methods including turning, milling, drilling, abrasive, abrasive waterjet and laser machining The issue of health and safety in machining FRP composites Machining of Polymer Composites is a must have book for practicing mechanical, manufacturing and production engineers, project managers and shop floor technicians .